Nonlinear dynamics. proceedings of the 34th IMAC, a Conference and Exposition on Structural Dynamics, 2016 /: proceedings of the 34th IMAC, a Conference and Exposition on Structural Dynamics, 2016. Volume 1 : ([2016]) - Unknown
No abstract available